A discussion on different techniques for GIS data collecting, precision, accuracy and quality of database - Paulo Cesar Lima Segantine; Rui António Ramos (European Regional Science Association (ERSA), 2004)
Nowadays, is a common sense the importance of geotechnologies in urban planning, transportation engineering and other different areas of knowledge. The Geographic Information System (GIS) is one of the geotechnologies that has been used increasingly. The collection of information and creation of a database are the most expensive, complex and important task in a GIS project. The collection of information results from the direct and indirect measurement of the real world. The reason for creating databases is to register and the maintain the different sources of collecting information. This paper has the objective to present the different techniques for data collection as input in GIS, as well as a brief discussion on the cost associated with the collection of data. Furthermore, comments on precision, accuracy and the quality of database are given.
Keywords: 330